Debatforum: Dannelsesbegrebet som element i folkehøjskolens selvforståelse - Pedersen, Kim Arne (Grundtvig-studier, 2006)
Debatforum By Ove Korsgaard, Kim Arne Pedersen & Anja Stokholm In the Debatforum readers are invited to respond to issues raised, or to raise new issues relative to the field of Grundtvig studies. Items submitted, preferably in the form of an article, may be of any reasonable length and in any of the languages usually accepted by the journal. In the contributions in Grundtvig-Studier 2006, Ove Korsgaard proposes that “ The future of the Danish folk high school depends upon a different understanding of its history from that which currently prevails”, Kim Ame Pedersen debates the Danish folk high school’s historical self-identification with the concept of Dannelse [development] as distinct from Uddannelse [education] and Anja Stokholm reflects upon the publication of a new edition of Gmndtvig’s sermons.